Bevacizumab-Irinotecan combination therapy in recurrent low-grade glioma, previously treated with chemo-radiotherapy: a case report - Castelli, Barbara; Fonte, Carla; Guidi, Milena; Tellini, Marco; Di Nicola, Marco; Iacono, Alessandro; Buccoliero, Anna Maria; Greto, Daniela; Genitori, Lorenzo; Sardi, Iacopo (Frontiers in Oncology, 2023)
Low grade gliomas (LGGs) of pineal region are usually difficult to remove and they frequently relapse or progress after front line chemotherapy. Bevacizumab-Irinotecan (BEVIRI) combination has been successfully attempted in children with recurrent LGGs, in most cases not previously irradiated. The efficacy of bevacizumab has also been described in radiation necrosis. Considering the possible overlapping of radiation treatment effect and disease progression and difficulty in differentiating, we report on the use of BEVIRI in a case of a recurrent relapsing low-grade glioma of the pineal region, subjected to multiple neurosurgical interventions, also treated with a carboplatin-etoposide regimen and a radiation course, at present at one-year follow-up showing a stable response, with no adverse events.